Measuring quality of life in clinical research – Part 1 - Priya Ranganathan; Jammbe Z Musoro; C. S. Pramesh (Perspectives in Clinical Research)
Health-related quality of life (HRQOL) is increasingly being recognized as an important outcome for individuals, both as part of clinical care as well as in research, along with conventional outcomes like response or survival. HRQOL includes several domains of functioning and is complex and difficult to measure. In this series of articles, we examine the concept of HRQOL and methods to measure it.